High performance liquid chromatography - Gilbert, Mary T. (Wright, 1987)
High Performance Liquid Chromatography focuses on the developments, operating techniques, practices, equipment, and packing materials involved in High Performance Liquid Chromatography (HPLC). The book first offers information on basic chromatographic theory, equipment, and the column. Topics include resolution, efficiency, pumps and gradient systems, connectors, detectors, injectors, column packing and testing, packing materials, and coupling of columns. The text also ponders on sample treatment and separation methods, as well as trace analysis, reversed phase chromatography, and selection/op.